Welcome to Teaching! Project on the Induction of Beginning Teachers - National Association of Secondary School Principals, Reston, VA.; National Association of Secondary School Principals, Reston, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
This booklet, reflecting the advice of those who have worked with the Project on the Induction of Beginning Teachers, contains lists of specific suggestions to aid teachers during their first year. There are five sections: (1) Summer, A Time for Preparing; (2) Orientation: Organize, Organize, Organize; (3) The First Semester: Mutual Adjustment; (4) Second Semester: Analysis and Growth; (5) A Word About Discipline. (SP 003 109 and SP 003 111 are related documents. A 150-frame, 25-minute filmstrip, "Thank God It's Friday," and accompanying record also available from the Association for $12.00. Three documents plus filmstrip and record, $13.50.) (JS)
Availability: Project on the Induction of Beginning Teachers, National Association of Secondary School Principals, 1201 16th St., N.W., Washington, D.C. (4/$1.00).
Sponsoring Agency: Carnegie Corp. of New York, NY.
Sponsoring Agency: National Association of Secondary School Principals, Reston, VA.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Beginning Teachers; Teaching